[Pat Dellinger Della, Architectural Engineering 1961]
Pat Dellinger Della, Architectural Engineering 1961, the first woman to graduate in architecture from Cal Poly. Photo included in Cal Poly Today article "A Tale of Cal Poly's First Four Women Architects" by Marlene Goldman, Summer 1981, which featured Joyce Dolman Vagasy, Connie Nash Brady (Architectural Design, 1962), and Ingeborg (Inge) Rose (Architectural Engineering, 1966).